2001
DOI: 10.1034/j.1399-0004.2001.590301.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural education and genetic counseling

Abstract: The responsibility to provide accessible, useful genetic counseling to individuals from many cultures and ethnicities arises from the increasing ethnocultural diversity of the populations served, coupled with the ethical goal of providing equal access and quality of services for all individuals. The multicultural education, training, and practice of genetic counseling involves three major components: knowledge of relevant ethnocultural groups, ethnocultural self-awareness, and an understanding of institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…16,27 Importantly, however, acceptance rates did not differ between women who received culturally tailored and standard genetic counseling. Cultural beliefs and values are increasingly being recognized as important factors in genetic counseling 18,19,28 and our recent study found that African American women who received culturally tailored genetic counseling were more satisfied with some aspects of counseling compared to those who received standard genetic counseling. 29 However, the effect of genetic counseling on BRCA1/2 test result acceptance was based on a limited number of women who completed pre-test counseling; thus, this finding should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,27 Importantly, however, acceptance rates did not differ between women who received culturally tailored and standard genetic counseling. Cultural beliefs and values are increasingly being recognized as important factors in genetic counseling 18,19,28 and our recent study found that African American women who received culturally tailored genetic counseling were more satisfied with some aspects of counseling compared to those who received standard genetic counseling. 29 However, the effect of genetic counseling on BRCA1/2 test result acceptance was based on a limited number of women who completed pre-test counseling; thus, this finding should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Culturally tailored genetic counseling (CTGC): The CTGC protocol provided the same education about hereditary cancer, genetic testing, and risk information as the SGC protocol after written informed consent was obtained. However, consistent with guidelines for providing culturally competent genetic counseling, 18,19 the CTGC protocol included standardized probes to elicit discussion about cultural factors that have been shown to influence decisions about genetic counseling among African American women in prior reports (e.g., spiritual and religious beliefs, communalism). 20,21 For example, women were asked what aspects of their spiritual and religious beliefs influence their decision to have genetic testing to facilitate discussion about the role of these factors in decision-making about genetic testing for BRCA1/2 mutations.…”
Section: Genetic Counseling Protocolsmentioning
confidence: 99%
“…An understanding of differences in ideas about kinship and inheritance, illness causality, and attitudes to prenatal diagnosis is recognized to be important for equitable and effective "cross-cultural communication" in the delivery of genetics services to multiethnic populations (Clarke and Parsons, 1997;Penchaszadeh, 2001;Shaw, 2003a;Weil, 2001). By comparison, there has been little discussion and assessment of current interpreting and translating provision in clinical genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional counseling has been predominantly designed for Euro-Americans, and the majority of genetic counselors are not members of ethnically diverse groups [1]. The purpose of this study was to explore the implications of multicultural genetics education in a traditional, non-Western community.…”
Section: Introductionmentioning
confidence: 99%